Foreign Capital Utilization in China : Prospects and Future Strategy - World Bank (Beijing, 2014)
China has been among the world's largest recipients of foreign direct investment (FDI). Nonetheless, at the time China is moving into its eleventh five-year plan period, four issues with FDI to China are becoming increasingly recognized by policy makers: geographic concentration, excessive reliance on investment in export-oriented manufacturing, under-investment in higher-technology industries, and heavy reliance on fiscal incentives to attract FDI. This report seeks to analyze these and provide benefit from international experience in suggesting policies. In addition to this introduction, the paper includes the following chapters: external environment, FDI in China, maintaining an attractive investment climate, leveling the playing field in taxation, improving the composition of FDI, and non-FDI capital flows liberalization and risk management.